Pengaruh Harga, Cita Rasa, Dan Kemasan Terhadap Kepuasan Konsumen Pada Canteen Anugerah School Sidoarjo - Yenny Hadi Murdjono; Handy Aribowo; Aloysius Jondar (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study aims to examine the effect of price, taste, and packaging both individually and simultaneously on customer satisfaction at Canteen Anugerah School Sidoarjo. The population taken is consumers of Canteen Anugerah School Sidoarjo aged 10 to 70 years who made purchases in the last 2 months. 76 respondents filled out the questionnaire and met the requirements. The variables in this study are price, taste, packaging, and customer satisfaction of Canteen Anugerah School Sidoarjo, with indicators, namely price affordability, price compatibility with product quality, price competitiveness, price compatibility with benefits, smell, taste, oral stimulation, packaging quality, packaging innovation, conformity to expectations, interest in visiting again, and willingness to recommend. Data collection methods using questionnaires. The data analysis used is Multiple Linear Regression Test. The results showed that the price variable (X1) was found to have a t value of 1.569 < 1.992 (t-table) and a sig. of 0.121> 0.05. From these results, it can be interpreted that price has no influence on customer satisfaction at Canteen Anugerah School Sidoarjo. The Taste variable (X2) is known to have a t value of 4.851> 1.992 (t-table) and sig. of 0.000 < 0.05 and the Packaging variable (X3) is known to have a t value of 5.195> 1.992 (t-table) and sig. of 0.000 < 0.05. From these results, it can be interpreted that Taste and Packaging have an influence on customer satisfaction at Canteen Anugerah School Sidoarjo.